2015
DOI: 10.1063/1.4934875
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of plasmon resonance tunneling through subwavelength hole arrays in highly doped conductive ZnO films

Abstract: Experimental results pertaining to plasmon resonance tunneling through a highly conductive zinc oxide (ZnO) layer with subwavelength hole-arrays is investigated in the mid-infrared regime. Gallium-doped ZnO layers are pulsed-laser deposited on a silicon wafer. The ZnO has metallic optical properties with a bulk plasma frequency of 214 THz, which is equivalent to a free space wavelength of 1.4 μm. Hole arrays with different periods and hole shapes are fabricated via a standard photolithography process. Resonant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 42 publications
(45 reference statements)
0
7
0
Order By: Relevance
“…n is then the density of valence electrons, and in ZnO the plasmon occurs as a broad peak centered at 18.9 eV [47]. However, in heavily doped samples with a significant amount of charge carriers in the conduction band, the conduction band can set up its own plasmon oscillation [48][49][50][51]. The energy of this conduction band plasmon can be described according to the above equation, with n being the density of electrons in the conduction band, hence the charge carrier concentration.…”
Section: Plasmon Analysismentioning
confidence: 99%
“…n is then the density of valence electrons, and in ZnO the plasmon occurs as a broad peak centered at 18.9 eV [47]. However, in heavily doped samples with a significant amount of charge carriers in the conduction band, the conduction band can set up its own plasmon oscillation [48][49][50][51]. The energy of this conduction band plasmon can be described according to the above equation, with n being the density of electrons in the conduction band, hence the charge carrier concentration.…”
Section: Plasmon Analysismentioning
confidence: 99%
“…Recently, increased efforts have focused on alternative plasmonic materials including Si, III-nitrides, and oxide semiconductors. Surface plasmons on oxide semiconductors (oxide-based SPRs) are expected to be successfully employed for optical applications in the infrared (IR) range. One particularly interesting material is metallic ZnO layers obtained by doping with Ga (Al) impurity atoms, , which have great potential due to their lower optical losses compared with noble metals in the IR range. It has been reported that surface plasmon resonances on the metallic ZnO (ZnO-SPRs) layers and nanostructures are excited from the near- to mid-IR range in terms of propagated- and localized-type surface plasmons, respectively. Of these structures, we have focused on film platforms for the development of biosensing applications with propagated-type SPRs. The benefits of large-area fabrications at lower cost render film platforms more attractive for industrial development compared to top-down methods for the fabrication of nanostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Specific TCO-based plasmonic devices have included on-chip waveguides, 19 perfect *Address all correspondence to: Justin W. Cleary, E-mail: Justin.Cleary.1@us. af.mil absorbers, 20,21 filters, 22 and modulators. 23 The plasmonic TCOs investigated so far are predominantly indium tin oxide and gallium-or aluminum-doped zinc oxide.…”
Section: Introductionmentioning
confidence: 99%